First contact : an exploratory study of the role of psychoanalytic infant observation in South African community psychology interventions - Lazarus, Jana (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Psychology))—University of Stellenbosch, 2007.